Pengaruh Akuntabilitas, Transparansi Sekolah dan Pengelolaan Keuangan Dana Bantuan Operasional Sekolah Terhadap Partisipasi Orang Tua Siswa - Suhesti Ningsih; Selvi Puspitasari; Abdul Haris Romdhoni (ITB AAS INDONESIA, 2022)
This study aims to determine the effect of accountability, transparency and financial management of BOS funds on the participation of parents of students in SD Negeri 1 Bendan, Banyudono Regency. The research population was 193 parents of SD Negeri 1 Bendan students. The research sample was selected using stratified random sampling method and then obtained a sample of 103 people. The research method is explanatory quantitative, namely research that will explain the relationship between variables that affect the researcher's hypothesis. The data collection method used a linkert scale questionnaire. The results showed that accountability, transparency and management of BOS funds had an effect on parental participation, this was evidenced by the F test which had a significance value of 0.000 0.05. The coefficient of determination of 0.738 means that accountability, transparency, and financial management of BOS funds have an influence of 73.80% on the participation of parents of students. While the remaining 26.20% is influenced by other variables not examined in this study.